Pre-Stroke Modified Rankin Scale: Evaluation of Validity, Prognostic Accuracy, and Association with Treatment - Quinn, Terence J.; Taylor-Rowan, Martin; Coyte, Aishah; Clark, Allan B.; Musgrave, Stanley D.; Metcalf, Anthony K.; Day, Diana J.; Bachmann, Max O.; Warburton, Elizabeth A.; Potter, John F.; Myint, Phyo Kyaw (Frontiers in Neurology, 2017)
Background and Purpose:The modified Rankin Scale (mRS) was designed to measure post-stroke recovery but is often used to describe pre-stroke disability. We sought to evaluate three aspects of pre-stroke mRS:validity as a measure of pre-stroke disability; prognostic accuracy and association of pre-stroke mRS scores and process of care. Methods:We used data from a large, UK clinical registry. For analysis of validity we compared pre-stroke mRS against other markers of pre-stroke function (age, comorbidity index, care needs). For analysis of prognostic accuracy we described univariable and multivariable models comparing pre-stroke mRS and other prognostic variables against a variety of outcomes (early and late mortality; length of stay; institutionalisation; incident complications). Finally, we described association of pre-stroke mRS and components of evidence-based stroke care (early neuroimaging, admission to stroke unit, assessment of swallow). Results:We analysed data of 2491 stroke patients. Concurrent validity analyses suggested statistically significant, but modest correlations between pre-stroke mRS and chosen variables (rho>0.40; p<0.0001 for all). Every point increase of pre-stroke mRS was associated with poorer outcomes for our prognostic variables (unadjusted p<0.001). This association held when corrected for other covariates. For example, pre-stroke mRS 4-5 OR:6.84 (95%CI:4.24-11.03) for one year mortality compared to mRS 0 in adjusted model. There was a difference between pre-stroke mRS and treatment, with higher pre-stroke mRS more likely to receive evidence based care. Conclusions:Results suggest that pre-stroke mRS has some concurrent validity and is a robust predictor of prognosis. This association is not explained by the influence of pre-stroke mRS on care pathways.